SISTEM INFORMASI SERVICE MOBIL BERBASIS WEBSITE MENGGUNAKAN METODE WATERFALL - Mely Mailasari; Monikka Nur Winnarto; Annida Purnamawati (Jurnal Teknoinfo, 2025)
The web-based car service information system aims to provide convenience in the process of recording and managing vehicle service online. This system was developed as a solution to the problem of managing service data which is still done conventionally using recording in a ledger resulting in data accumulation and inefficiency as well as unpredictable service customer queues. With this web-based system, customers are given the convenience of accessing service information and booking service schedules without having to visit the workshop directly and officers find it easier to manage service transaction data, check car spare part stock and create reports. The development of this system uses the waterfall method which includes needs analysis, system design, design, implementation and testing. With this system, it is expected to improve the operational efficiency of the workshop for workshop employees and make it easier for customers to access service information.